Ester synthesis mechanism and activity by Bacillus licheniformis, Candida etchellsii, and Zygosaccharomyces rouxii isolated from Chinese horse bean chili paste. (12th April 2021) - Yang, Linzi; Li, Xueli; Lu, Yunhao; Lv, Yuanping; Chi, Yuanlong; He, Qiang
Abstract: BACKGROUND: Esters are indispensable aroma compounds and contribute significantly to the fruity aromas in fermented condiments. The ester synthesis activity and pathways of Bacillus licheniformis, Candida etchellsii, and Zygosaccharomyces rouxii, isolated from Chinese horse bean chili‐paste (CHCP), were investigated. Chemical buffer models containing esterification and alcoholysis systems inoculated with extracellular extracts of these three strains were established. RESULTS: The ester synthesis activity of C. etchellsii was stronger than that of the other two strains. Zygosaccharomyces rouxii could synthesize acetate esters via esterification, whereas the biosynthesis pathways of B. licheniformis and C. etchellsii were esterification and alcoholysis. Esterification exhibited relatively high activity at pH 4, whereas alcoholysis activity improved with an increase in the pH from 4 to 8. Candida etchellsii could synthesize C6 –C8 of acetate esters, and its activity improved with the number of alcohol carbon atoms. These three strains could synthesize C10 –C18 of ethyl esters. Their ethyl ester synthesis activity decreased with the aliphatic acid carbon number. CONCLUSION: Candida etchellsii has the potential to be used in CHCP fermentation to accumulate esters and improve flavor compared with the other two strains. This research is helpful in explaining the mechanism of ester synthesis in fermented condiments. © 2021 Society of Chemical Industry.